Analisis Wujud Masalah Sosial dalam Film Kokuhaku karya Tetsuya Nakashima (Kajian Sosiologi Sastra) - Poppy Rahayu; Frida Philiyanti; Farah Krisna Dewi (Chi'e: Journal of Japanese Learning and Teaching, 2022)
This study aims to determine what forms of social problems exist in Tetsuya Nakashima's Kokuhaku film. These causal factors trigger these problems and how to solve the problem using a literary sociology approach. This study employs Wellek and Warren's sociological theory of literary works and Soekanto's theory of existence, sources, and techniques for solving social problems. This study employs a descriptive-analytic method and data gathering procedures gleaned from a literature review. According to the study's findings, there are 27 social problems in Tetsuya Nakashima's Kokuhaku film, including 15 data on societal norm violations in the form of child delinquency, eight difficulties with family disintegration, three crime problems, and one bureaucracy problem. In this video, two causes generate social problems: psychological factors and cultural aspects. Authoritarian measures solve the majority of the social problems in this film.